AGE-DEPENDENT HYPERTENSION AND VASCULAR REMODELING IN DAHL-S RATS ARE ASSOCIATED WITH ELEVATED LEVELS OF MARINOBUFAGENIN AND COGNITIVE DECLINE. (June 2018) - Fedorova, O.; Grigorova, Y.N.; Hagood, M.; Mcdevitt, R.; Long, J.; Mcpherson, R.; Naraine, A.; Juhasz, O.; Wei, W.; Zernetkina, V.; Petrashevskaya, N.; Fishbein, K.W.; et al.
Abstract : Objective: Age-associated hypertension and central arterial stiffening contribute to cognitive impairment. Increase in blood pressure (BP) and aortic remodeling occur in Dahl salt-sensitive rats (Dahl-S) with an advancing age even on a normal salt intake. Marinobufagenin (MBG), a novel pro-hypertensive factor, is implicated in Dahl-S hypertension. Here we determined whether age-associated arterial remodeling and hypertension implicate in cognitive decline in Dahl-S and whether these changes are accompanied by an increase in pro-hypertensive and pro-fibrotic factor MBG. Design and method: Male Sprague-Dawley rats (S-D) and Dahl-S were kept on a normal 0.5% NaCl intake (n = 8/14 per group) for the duration of the study. Systolic BP (SBP), pulse wave velocity (PWV), MBG, aortic collagen, and behavioral tests (open field test (OFT); novel object test; redundant place-cue version of the Morris water maze test (MWM); rotarod test) were assessed in 3-mo and 12-mo animals. Results: At 3-mo Dahl-S had higher SBP, PWV and aortic wall remodeling vs. 3-mo S-D. Between 3 and 12-mo both S-D and Dahl-S exhibited an increase in SBP, PWV, MBG and aortic wall collagen deposition. These parameters were significantly higher in 12-mo Dahl-S than in age-matched S-D (Table). MBG correlated with SBP in Dahl-S only (Pearson R = 0.52, p = 0.04), and with PWV in both S-D (Pearson R = 0.37, p = 0.01) and Dahl-S (Pearson R = 0.54, p = 0.04). Behaviorally, in an MWM, 12-mo DSS demonstrated impaired spatial hippocampal memory vs. 12-mo S-D. Compared to 3-mo, both 12-mo S-D and Dahl-S demonstrated an age-dependent decline in OFT activity, but 12-mo Dahl-S were more active in OFT, had more endurance during the rotarod test indicating non-impaired motor coordination, and showed increased object exploration vs. age-matched S-D (Table). Performance in behavioral tests by 12-mo hypertensive Dahl-S may suggest the development of age-associated anxiety and change in emotional status, and a decline in their spatial hippocampal memory. Conclusions: Cognitive deficit in aged hypertensive Dahl-S is limited to hippocampal-dependent spatial memory. In Dahl-S, development of age-dependent hypertension and aortic wall remodeling, occurred in context with an increase in MBG, may contribute to hippocampal spatial memory impairment, and suggested a possible implication of MBG in these declines. Figure. No caption available.